Socio-Religious-Based Critical Digital Media Literacy for Disengagement from Radicalism for Ex-Terrorist Convicts - Mala, Faiqotul; Rahman, Fazlul; Marhumah, Ema; Danarta, Agung (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This article aims to analyze the influence of the Internet on the involvement of former terrorist prisoners, as well as formulate a Socio-Religious-based Digital Media Literacy model that can support the process of disengagement from radicalism. To help this research provide a comprehensive picture, this study interviewed one female former terrorist inmate and her companion after being released from prison, as well as a representative from Ruangobrol.id. This organization cares for former terrorist inmates to become "credible voices" in educating the public about terrorism. This research uses disengagement theory and critical digital literacy to analyze data generated from interviews with sources and other supporting sources. The study found that there is a duality of the Internet's function towards radicalism; the Internet is a tool that can introduce the poison of radicalism to someone, but at the same time, the Internet can also function as an antidote to the poison, helping people who are exposed to it to escape radicalism. In conclusion, this study proposes the formulation of a "socio-religious-based critical digital media literacy" that combines technical and socio-religious skills to maximize the antidote function of the Internet.